Paul S Lloyd: Food and Identity in England, 1540–1640: Eating to Impress - Wilkins, John (Petits Propos Culinaires, 2018)
Paul S Lloyd: Food and Identity in England, 1540–1640: Eating to Impress: Bloomsbury, 2015: 260 pp., paperback, £28.99.